PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS Vb SDN 026 BANJAR XII KECAMATAN TANAH PUTIH - Damanik, Susanti; Noviana, Eddy; Putra, Zetra Hainul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research of the background by lowering of result learn social science class student of Vb SDN 026 Banjar XII with mean 55,25 with complete critery on minimize (KKM) ips is 65, total class student of Vb is 20 tired people with KKM only 8 people completely classical 40% this research represent research of class action (PTK) with aimto to increase result of learning IPS class student of Vb SDN 026 Banjar XII by applying model Numbered Heads Together data collecting instrument at this thesis is activity sheet learn and student and also result of meaning. Is obtained by result of activity learn in course of study at first cycle of first meeting is 58,3% and at second meeting mounting 12,5% becoming 70,8% . at cycle both of activity learn more mounting of cycle of first,cycle siclus both of first meeting mount counted 12,5% becoming 83,3% at meeting both of second cycle mounting counted 12,5% becoming 95,8%.The result of data analysis of activities first cycle student at first meeting is 54,2% and second meeting mounting counted 8,3% becoming 62,5% at cycle both of first meeting of student activity mount from 16,7% becoming 79,2% and at the meeting both of second cycle mounting from 12,5% becoming 91,7%. A thesis this present result learn which is obtained from daily restating value before action with daily restating mean before action with mean 55,25 daily restating average value mount equalto 26,24% becoming 69,75. At this cycle of daily restating average value mount from 47,96% becoming 81,75 the principle result of research with applying of model study of type cooperative of Numbered Heads Together can improve result learn class student social science of Vb SDN 026 Banjar XII Kecamatan Tanah Putih.Keyword: numbered heads together, social studies learning outcomes